2016
DOI: 10.1093/jxb/erw166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of down-regulating ornithine decarboxylase upon putrescine-associated metabolism and growth inNicotiana tabacumL.

Abstract: HighlightRNAi-mediated reduction of ornithine decarboxylase gene activity in tobacco has negative effects on plant growth and leads to widespread alterations in primary and secondary metabolism, particularly in wounded plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 93 publications
(142 reference statements)
1
33
0
Order By: Relevance
“…LA plants with the highest total polyamine content showed the most severe impairment of leaf maturation, characterized by weak senescence, a higher chlorophyll content, and more leaf mesophyll cells per unit area (Figure 1 2005). ODC is the main enzyme responsible for putrescine biosynthesis in tobacco roots and plays a key role in the production of nicotine and the overall alkaloid profile (Chintapakorn & Hamill, 2007;Dalton et al, 2016;DeBoer et al, 2011DeBoer et al, , 2013. Topping of tobacco plants allows the crop to reach its full yield and quality potential at harvest and leads to increased activity of ODC and several enzymes in the nicotine biosynthesis pathway, including putrescine methyltransferase and quinolinate phosphoribosyltransferase, in tobacco roots 24-48 hr after topping (Mizusaki, Tanabe, Noguchi, & Tamaki, 1973;Saunders & Bush, 1979 where ADC rather than ODC is responsible for putrescine biosynthesis (Figure 4a), DFMO treatment resulted in a significantly higher total polyamine content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LA plants with the highest total polyamine content showed the most severe impairment of leaf maturation, characterized by weak senescence, a higher chlorophyll content, and more leaf mesophyll cells per unit area (Figure 1 2005). ODC is the main enzyme responsible for putrescine biosynthesis in tobacco roots and plays a key role in the production of nicotine and the overall alkaloid profile (Chintapakorn & Hamill, 2007;Dalton et al, 2016;DeBoer et al, 2011DeBoer et al, , 2013. Topping of tobacco plants allows the crop to reach its full yield and quality potential at harvest and leads to increased activity of ODC and several enzymes in the nicotine biosynthesis pathway, including putrescine methyltransferase and quinolinate phosphoribosyltransferase, in tobacco roots 24-48 hr after topping (Mizusaki, Tanabe, Noguchi, & Tamaki, 1973;Saunders & Bush, 1979 where ADC rather than ODC is responsible for putrescine biosynthesis (Figure 4a), DFMO treatment resulted in a significantly higher total polyamine content.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the ADC route to putrescine has only a minor effect on the alkaloid profile of tobacco whereas the ODC pathway plays the major role in nicotine biosynthesis (Chintapakorn & Hamill, 2007;Dalton et al, 2016;DeBoer, Dalton, Edward, & Hamill, 2011;DeBoer, Dalton, Edward, Ryan, & Hamill, 2013). Putrescine is converted to spermidine and then spermine by the successive addition of aminopropyl groups derived from decarboxylated S-adenosylmethionine (SAM), in reactions catalyzed by the enzymes spermidine synthase and spermine synthase, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective gene transfer procedures in many plant species have enabled DNA disruption, RNAi-mediated or viral-induced gene silencing protocols to be developed for researchers wishing to study the role of any given gene in a developmental or biochemical process (e.g., [166] and references therein). Transformation procedures have been reported for some resurrection species, such as the well-studied dicotyledenous species C. plantagineum [167] and also L. brevidens [168].…”
Section: Direct Dna Manipulation Of Desiccation-related Genesmentioning
confidence: 99%
“…The development of molecular biological approaches has been fruitful (5,13,14) but is challenging where the enzymology is completely unknown. An alternative "retro-biosynthetic" approach involves the measurement and interpretation of the natural fractionation in 2 H or 13 C isotopes during the course of biosynthetic reactions.…”
mentioning
confidence: 99%